Don't Waste Your Time in the Countryside. (July 2016) - Schumacher, Patrik
Abstract : With the countryside becoming ever more sparsely populated as fewer people are needed to keep rural enterprises running, is there any point in engaging architects there?Patrik Schumacher, partner at Zaha Hadid Architects, argues that their time and skills are put to better use in cities, where buildings impact a far greater number of individuals and their social and cultural functionality is more important. Engineers, meanwhile, are perfectly equipped to devise generic solutions for the rural realm.